## Solving the Equation: 0.2(x + 2y) - 0.3(2x - y) = 3.5

This article will guide you through the steps of solving the linear equation: **0.2(x + 2y) - 0.3(2x - y) = 3.5**. We'll break down the process to make it easy to understand.

### 1. Distribute the coefficients:

Begin by distributing the coefficients outside the parentheses:

**0.2x + 0.4y - 0.6x + 0.3y = 3.5**

### 2. Combine like terms:

Next, combine the 'x' terms and the 'y' terms:

**(-0.6x + 0.2x) + (0.4y + 0.3y) = 3.5****-0.4x + 0.7y = 3.5**

### 3. Isolate 'x' (or 'y'):

Now, you can choose to isolate either 'x' or 'y'. Let's isolate 'x' for this example:

**-0.4x = 3.5 - 0.7y**

### 4. Solve for 'x':

Divide both sides by -0.4 to get 'x' by itself:

**x = (3.5 - 0.7y) / -0.4**

### 5. Simplify (Optional):

You can simplify the expression further if needed:

**x = -8.75 + 1.75y**

### Conclusion

The equation **0.2(x + 2y) - 0.3(2x - y) = 3.5** has been solved for 'x'. The solution is **x = -8.75 + 1.75y**. Keep in mind that this solution expresses 'x' in terms of 'y'. To find a specific value for 'x', you would need to substitute a value for 'y'.